OPTIMASI PEMILIHAN INGREDIEN DAN ALOKASI PENYIMPANAN BAHAN - David Yunianto; Abdullah Shahab (Jurnal Teknobisnis, 2005)
The adverse climate of a business competition, especially in the realm of production of household commodities, enforces a business enterprise to apply a strategic decision about mixing ingredient and its inventory effectively. This decision entails the appropriate selection of ingredient within a minimum attainable cost.Optimization of ingredient selection and inventory was carried out in a detergent industry. Optimization was conducted employing the technique of Linear Programming with the incorporation of several relevant constraints. The optimization was focused on the optimal profit, taking account specifically the cost of material handling; this would necessitate the choice of suitable ingredients for manufacture of a certain product, and a decision about where these ingredients would be inventoried.In this study, the optimization was proven capable to increase the profit in a significant figure. The results of the optimization determined specifically the selection of the ingredients for each product according to the quality specified, and at the same time determined the allotment of the ingredients in the specified inventory.